2009
DOI: 10.1111/j.1939-1676.2009.0283.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofEnterococcus faeciumSF68 Probiotic on Giardiasis in Dogs

Abstract: Background: Giardiasis is a common, potentially zoonotic disease, and dogs often harbor and shed cysts without showing clinical signs. Treatment with the probiotic Enterococcus faecium SF68 has been shown to stimulate mucosal and systemic immunity in a variety of animal models and in young dogs, and to reduce giardial cyst and antigen shedding in rodents.Hypothesis: Adult dogs with chronic naturally acquired giardiasis will have decreased giardial fecal cyst and antigen shedding and increased innate and adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…fecal and serum IgA concentration) function. Similarly, one study showed that the administration of the probiotic E. faecium SF68 for 6 weeks did not change fecal IgA concentrations in adult dogs with chronic giardiasis (Simpson et al ., ). In contrast, an increase in fecal IgA in young dogs has been described after oral administration of the same probiotic strain (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…fecal and serum IgA concentration) function. Similarly, one study showed that the administration of the probiotic E. faecium SF68 for 6 weeks did not change fecal IgA concentrations in adult dogs with chronic giardiasis (Simpson et al ., ). In contrast, an increase in fecal IgA in young dogs has been described after oral administration of the same probiotic strain (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…However, several studies have reported a positive effect of probiotics on the treatment of giardiasis [67,[69][70][71]. Silymarin used as a supplement to anti-protozoal drugs…”
Section: Opinionmentioning
confidence: 98%
“…For example, dogs with giardiasis may have been included in the study because parasitological screening was not performed. A study of E. faecium SF68 in dogs with subclinical giardiasis indicated that the probiotic had no effect on cyst shedding, which may indicate a lack of efficacy for the species E. faecium in clinical giardiasis. Inclusion of dogs with clinical giardiasis in our study could have led to underestimation of the efficacy of the ADPP in dogs with nonparasitic diarrhea, although it is likely that their inclusion rate, and consequently their impact on study findings, was low .…”
Section: Discussionmentioning
confidence: 96%